FORECASTING FUTURE PRODUCTION TREND OF DRAGON FRUIT IN REGION 10, PHILIPPINES - Javier, Joemar Dayham (Socio-Economics/Agribusiness Department, 2024)
This research provided an in-depth analysis of the future production trends of dragon fruit in region 10, Philippines, using secondary data from the Philippine Statistics Authority. Employing statistical methods like descriptive statistics, trend analysis, time series analysis, ARIMA modeling, and cross-validation, the study revealed a steady increase in dragon fruit production from 2012 to 2022. It forecasted continued growth based on linear regression but cautioned about potential declines as indicated by ARIMA modeling. The research underscored the necessity of appropriate modeling for accurate forecasts and highlighted the influence of external factors on production trends. It aimed to guide farmers, policymakers, and stakeholders in strategic decision-making for the region's dragon fruit industry.